Serial Native T1 Mapping to Monitor Cardiac Response to Treatment in Light-Chain Amyloidosis. (October 2016) - Hur, David J.; Dicks, Demetrius L.; Huber, Steffen; Mojibian, Hamid R.; Meadows, Judith L.; Seropian, Stuart E.; Baldassarre, Lauren A.
Abstract : Supplemental Digital Content is available in the text.